Exploring black women's diverse hairstyles through art: a case study - Radebe, Zanele Lucia (Vaal University of Technology, 2019)
Problem statement This study investigates black women’s diverse hairstyles through art. The main research question is: How can black women’s diverse hairstyles be understood through art to appreciate the meaning attached to these hairstyles? The research question is informed by a black feminist theory. Objectives of the study Based on the research problem, the objectives of the study were first, to find out how black women’s diverse hairstyles could be understood through art to appreciate the meanings attached to these hairstyles. Secondly, to examine similarities and/or differences between how Lebohang Motaung (hereinafter referred to as Motaung) and Lorna Simpson (hereinafter referred to as Simpson) construct and express meanings of diverse hairstyles in their artworks. This was done by means of analysing the two artists’ artworks. Thirdly, to find out what or who influences Motaung’s choice of hairstyles, which was done by conducting an in-depth individual interview with Motaung. Fourthly, to find out what or who influences Simpson’s choice of hairstyles, which was done by reviewing the literature on Simpson. Fifthly, to explore how Motaung and Simpson interpret their physical appearance based on their hairstyles. Research design and methodology The empirical investigation focused on analysing black women’s diverse hairstyles by means of analysing artworks of Motaung (black South African female artist) and Simpson (black American female artist). This study contextualises black women’s artworks as visual responses to patriarchal, social subjugation and objectification of black women’s hair, by using black feminist epistemology through artistic production. Data collected through visual material were analysed using Barnet’s (2011:37-38) critical analysis of artefacts strategy. Barnet’s steps of critical analysis include description of the artefact, interpretation of the artefact, analysis of the artefact and personal report. The analysis of the artworks enabled the researcher to compare and contrast the artworks of the two selected participants. The researcher first analysed the black South African contemporary female artist, Motaung’s (b.1992), work as a visual form of resistance to masculine control of images of black women’s hairstyle representations and self-definition. The researcher believes that Motaung creates self-defined artworks that appreciate the beauty of black women’s hair and she demystifies the ambiguous meaning attached to black hairstyles. Secondly, Simpson’s (b.1960) artworks were analysed in the study to understand what or who influences her choice of hairstyles. The researcher found it appropriate, for her study, to focus on Simpson, because she is a prominent contemporary black American feminist artist, who explores the concept of black hairstyles, focusing on themes such as race, gender and identity formation. Furthermore, one in-depth, individual interview was conducted with Motaung. The analysis was based on black feminism that enabled the researcher to listen to Motaung’s views and be part of her portrayal of black women’s diverse hairstyles. The qualitative data collection and methodology were guided by ethical considerations of the Vaal University of Technology for undertaking research. Ethical procedures were followed regarding selected participants for both artwork analysis and the interview. Five themes emerged from this analysis, namely Motaung’s personal background, black hair politics, conceptual work, choice of medium and working process, art influencers and artwork clarification. Black women’s diverse hairstyles In contemporary times, black women’s hairstyle representations are highly politicised as black people strive to reclaim their identities. The changing meaning of what is good hair for black women is highly controversial; some black women consider natural hairstyles as good and authentic hair for black women, because they embrace the Afrocentric beauty standard that was degraded by whites since the colonial era. On the other hand, other black women are comfortable with altered hair that is viewed as a European beauty standard, because altered hair has become part of black women’s culture and identity. The literature review suggests that historically, narrow European-centric beauty standards have deemed black women’s natural features as unattractive and unprofessional, especially their textured, curly to kinky hair. These restrictive ideals have left black women in a compromised position, having to adhere to certain societal norms for the sake of upward mobility, whether that is getting ahead professionally or fitting into a myriad of social environments in which they can be accepted. Main findings From the literature review, the study found that there are controversial viewpoints regarding what is or is not suitable for black women in terms of their hairstyles. The controversy led to black women’s hairstyles being discussed constantly in binary opposition of good/ bad hair, natural/ unnatural, Afro-centric/ Eurocentric, authentic/ inauthentic, African/ Western, low/ high self-esteem, amongst others. The literature further indicates that there is a need to conduct a study that embraces diverse (both natural and unnatural) hairstyles to get rid of the politics, oppressions and binary oppositions placed on black women’s hairstyles. From the analysis of the two artists, Simpson’s works were found suitable for this study because her body of work links with that of Motaung’s, in terms of concept, style, theory, content and technique, despite the fact that these artists are located in different geographical contexts and settings. From the individual interview, the study found that Motaung was prompted by black hair politics, such as the politics of exclusion of black hairstyles, such as afros and braids in educational institutions and work places. Such politics inspired her to create artworks on black women’s diverse hairstyles. Motaung focused on natural hairstyles because she wanted black women to see what they can do with their natural hair. By using natural hairstyles, Motaung wanted to challenge the misconception that natural hair is not beautiful. The study also found that Motaung focused on unnatural hairstyles because there is bias against black women who wear synthetic hair. Motaung created artworks using synthetic hair to make a bold statement that synthetic hair is not fake hair but rather extra hair, which black women can use to self-express and self-define. Recommendations ● The study recommends that self-definition is a black feminist strategy that black women can use to self-insert and self-represent using diverse hairstyles. The act of insisting on black women’s self-definition validates black women’s power as human subjects, against structural patriarchal forces and beauty standards that are continuously set for black women. ● The study recommends that it is significant for black women to embrace diverse hairstyles, to get rid of the politics, oppressions and binary oppositions placed on black women’s hairstyles. ● From the artworks of Motaung and Simpson, the study recommends that it is significant for black female artists to produce artworks on diverse hairstyles to diminish oppressive structures that are placed on black women’s hairstyle representations.
M. Tech. (Department of Visual Arts and Design: Fine Arts, Faculty of Human Sciences), Vaal University of Technology.
Keywords: Back women hairstyle; Black feminism; Artworks; Diverse hairstyles; Dissertations, Academic -- South Africa.; Hairstyles -- South Africa.; Hair in art -- Exhibitions.; Women, Black, in art.